New drugs in Europe, 2012: EMCDDA-Europol 2012 annual report on the implementation of Council Decision 2005/387/JHA : in accordance with Article 10 of Council Decision 2005/387/JHA on the information exchange, risk assessment and control of new psychoactive substances (Joint reports, 2013)
The unprecedented growth in the number, type and availability of new drugs over the past few years has seen the phenomenon take on global significance. Overall, the number of substances notified in the last two years accounts for more than half of the total number of substances notified to the EU Early warning system since May 2005. Driven by globalisation, technological advancement and the Internet, an open market for new drugs has now developed which presents challenges to public health, law enforcement and policy making. The rapid appearance of non-controlled alternatives to controlled drugs underlines the ability of the market to respond to changes in the legal status of psychoactive substances and has been accompanied, in some cases, by serious adverse health consequences. It is well established that organised crime is involved in some of these activities and continues to exploit the opportunities presented by the market in new drugs. This report presents the key activities performed by the EMCDDA and Europol in 2012 and includes details of all the relevant activities in support of the implementation of Council Decision 2005/387/JHA on the information exchange, risk assessment and control of new psychoactive substances.